Ensino sobre idosos nos cursos de graduação em nutrição : o panorama brasileiro - Martins, Renata Breda (2019)
Introduction: Brazil experiences a process of demographic transition in which there is an increase in the elderly population to the detriment of adults and children. This fact challenges the government, educational institutions and society, to reorganize itself to respond to the needs of this population. Higher Education Institutions (HEI) should insert teaching about the elderly in the curriculum of the courses, to contribute to the training of professionals. Objective: To describe the panorama of teaching about the elderly in undergraduate courses in Nutrition of brazilian higher education institutions. Methods: This was a cross-sectional study, whose data were obtained from the e-mail addresses of the HEI accredited in the electronic system of the Ministry of Education (e-MEC) in 2018. The search was carried out in curriculum grid, curriculum, political-pedagogical project about the presence of discipline(s) with the term(s): elderly, elder, aging, geriatrics, geriatric, gerontology, third age. We excluded the HEI that did not offer electronic access, and the courses offered exclusively in the distance teaching mode. The following variables were investigated: administrative category; academic organization; electronic address of the HEI in e-MEC; course modality; evaluation in the National Student Performance Exam (Enade) 2016; Enade concept; minimum course load per e-MEC; curriculum grid; year of beginning of the valid curriculum; the hourly course load reported by the HEI; disciplinary committee; disciplines involving the elderly; type of disciplines; nature of the disciplines; offer semester; hours of the disciplines involving the elderly; pedagogical activity of these disciplines; internship in the area of the elderly. As well as, to analyze the association between the availability of disciplines involving the elderly and the Brazilian geographic regions and the proportion of undergraduate courses in Nutrition with the discipline that involve the elderly in relation to the number of elderly people in the regions. Results: A total of 527 HEIs were analyzed, mostly private HEIs, 88.0% (n= 464), 41.7% (n= 220), and 86.3% (n= 455). Data from 447 HEI were obtained, of which 64.0% (n=286) of the HEI offered subjects on the elderly, and 58.1% (n=166) were offered in a shared way (not only involving the subject of the elderly), 76.2% (n=166) from the 5th to the 8th semester, 53.2% (n=75) was of a theoretical nature, 61.5% (n=163) had ≥60 hours/semester, 92.2% (n=247) constituted a compulsory pedagogical activity. It was identified that 97.2% (n=239) of the curricular grades started to apply between 2010-2018 and 98.6% (n=350) had a time load ≥3200 hours. It was observed that the stage involving the elderly (one or more) was offered by only 4.6% of the courses. The Southeast region presented the highest number of HEI, 37.4% (n=195). The North region presented the highest proportion of courses with the discipline in relation to the number of elderly people. Conclusion: In the present study, approximately 1/3 of Brazilian HEIs don’t offer teaching about the elderly in their undergraduate courses in Nutrition neither as a discipline nor as an internship. In this case, the disciplines that addressed the theme of the elderly were offered in a shared way with other subjects, had a theoretical approach, a semester load of ≥60 hours and were obligatory. Only a minority of the institutions provided internships in this area.